ANALISIS KANDUNGAN SAPONIN PADA DAUN DAN TANGKAI DAUN Carica pubescens Lenne & K. Koch - Minarno, Eko Budi (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2016)
Carica pubescens Lenne K. Koch is a tropical species that adapt to the plateau environment and low temperatures. In East Java, the plant is found in Cangar and Bromo region. Morphological, chemical content, and analysis of protein banding pattern on C. pubescens has been done, but more on the analysis of active compounds for pharmaceutical raw materials and its accumulation in the body of the plant has not been widely studied. Saponins on C. pubescens potential as a raw material of natural medicine in the treatment of Diabetes Mellitus (DM). This study aims to determine the content of saponin in leaf and petiole of C. pubescens in terms of absorbance values. Saponins were analyzed by qualitative form the foam test, color test, Thin Layer Chromatography (TLC) analytical and preparative. Quantitative test in the form of UV-Vis spectrophotometry results preparative TLC. This research was done at the Laboratory of Department of Biology and Chemistry UIN Maulana Malik Ibrahim Malang. The results showed that the leaf and petiole of C. pubescens positive for the saponins with the formation of stable foam for 60 seconds at 1.5 cm - 1.7 cm. The third positive samples containing saponins triterpene the ring test produces a brownish color. Isolation saponin by TLC shows the best ratio of eluent chloroform: methanol: water (14: 6: 1) compounds can be separated perfectly. Saponin absorbance values obtained three samples as follows: petiole samples from the region Cangar amounted to 0.852, leaf samples from the region Cangar amounted to 0.686, and leaf samples from Bromo region amounted to 0,629. The highest saponins found in organs petiole. Thus the petiole of C. pubescens has the potential to be used as a source of triterpene saponins which can be developed into a commercial herbal medicines.